Perspectives on the learning and teaching of spelling - Radzuwan, Ab Rashid; Dheifallah, Altamimi; Omar, Ali (2019)
English Language Teaching, in the past, has given very little emphasis on spelling and the teaching and research of it. This paper starts by providing a background on the teaching of spelling. A brief history of the developments in the teaching of spelling from the 1930s to 1940s is followed by an illustration on why there are important issues on spelling that need to be addressed from within the Arab context. An overview of research done on Arab learners spelling is discussed. The main part of this review which discusses the impact of the ideas of Piaget and Vygotsky on; i) learning, in general; and ii) the teaching and learning of spelling are presented. This is then followed by a critical appraisal of recent research done on the teaching of spelling where the influences of constructivism in the teaching of it are evident. The article concludes with implications of these constructivist movements in the teaching of spelling on learners.